Exercising the Sleepy-ing Brain: Exercise, Sleep, and Sleep Loss on Memory. Issue 1 (January 2022) - Roig, Marc; Cristini, Jacopo; Parwanta, Zohra; Ayotte, Beatrice; Rodrigues, Lynden; de Las Heras, Bernat; Nepveu, Jean-François; Huber, Reto; Carrier, Julie; Steib, Simon; Youngstedt, Shawn D.; Wright, David L.
Abstract : This article discusses emerging evidence supporting functional interactions between exercise, sleep, and sleep loss in memory processing. Abstract : We examine the novel hypothesis that physical exercise and sleep have synergistic effects on memory. Exercise can trigger mechanisms that can create an optimal brain state during sleep to facilitate memory processing. The possibility that exercise could counteract the deleterious effects of sleep deprivation on memory by protecting neuroplasticity also is discussed.